Factors associated with episiotomy among parturients delivering in a tertiary care centre in Nigeria - Owa, Olorunfemi Oludele; Eniowo, Akinbowale Romance; Ilesanmi, Olayinka Stephen (International Journal of Research in Medical Sciences, 2017)
Background: The use of routine episiotomy is now less favoured among obstetricians. Given considerable evidence, it use increases maternal morbidity without evidence to support maternal or neonatal benefit. Objectives: To determine the current rate of episiotomy among parturients delivering at Federal Medical Centre, Owo, Ondo State, Nigeria and to identify factors associated with episiotomy. Methods: The retrospective study was conducted using the delivery records between 1st January 2012 and 31st December 2012. Information was obtained from the delivery register and medical records. There were 802 booked patients who had singleton vaginal deliveries between the studied periods. A total of 728 of these patients’ case records were obtained for analysis using SPSS 17. Results: The incidence of episiotomy was 9.3%. Those age <20 years, nulliparous, those who had assisted breech and instrumental deliveries had more episiotomy (P <0.0001). All the instrumental deliveries and most assisted breech deliveries (67%) were taken by the doctors. Episiotomies were more common when doctors took deliveries (Doctor vs. Nurses: 28.6% vs. 5.8%) (P <0.0001). Conclusion: While this study has identified factors associated with episiotomy, the episiotomy rate remain within normal rate at the studied centre. It is pertinent that health care providers always bear in mind the standard indications for episiotomy. This will go a long way in reducing the episiotomy rate and maintaining the recommended WHO rate of 10%.